Pemaknaan Ni’mal Abdu Dalam Quran : Studi Tafsir Al Munir Wahbah Az-Zuhaili - Adirasa, Ery Santika; Zadittaqwa, Mohammad; Fitriani, Laily (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2024)
One interesting word that catches attention is "ni'mal abdu" (the best servant), which is repeated only twice in the Quran, specifically in Surah Saad: verse 30 and 44. This word is a praise from Allah bestowed upon Prophet Solomon and Prophet Job (Ayyub). Both prophets have different backgrounds, with Prophet Solomon being blessed with wealth, while Prophet Job was tested with calamities. However, both of them are honored as the best servants. This research aims to describe the messages contained in these verses to understand what makes someone fall into the category of ni'mal abdu.This study utilizes a qualitative research method with library research as the approach. The data analysis employs content analysis. In this written work, the author will document the interpretation of ni'mal abdu according to the views of Wahbah Az-Zuhaili, a commentator in Tafsir Al Munir, and then elaborate on it. The primary data source used is the Quran and Tafsir Al Munir, while secondary data sources include relevant books and journals on the topic.The research findings indicate that the meaning of ni'mal abdu (the best servant) can be derived from two situations based on the stories of Prophet Solomon and Prophet Job. Immense wealth does not necessarily imply exceeding limits, but if it is approached with gratitude and obedience, it becomes the potential of a good servant in the sight of Allah, as exemplified by Prophet Solomon. On the other hand, if someone is tested with a lack of wealth or afflicted with hardships, but responds with patience and remains obedient to Allah, they also have the potential to become a good servant in the eyes of Allah, similar to Prophet Job.